Kinerja Penyuluh Pertanian Kabupaten Bandung Dalam Menjalankan Tugas Dan Fungsinya - Fauziyyah, Azka Nadia; Hapsari, Hepi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Law 16/2006 regulates agricultural development and agricultural extension processes. Bandung Regency is one of the regions with great agricultural potential. There are 160 agricultural extension workers in Bandung Regency helping an average of 2-3 villages. In fact, in the Law on the Protection of Farmers' Rights No. 19/2013, the extension officer in charge of the assisted community. In the performance report of the Bandung Regency Agriculture Office (2021), it was stated that the target does not match the actual performance of the land. The purpose of this study is to evaluate the professional achievements of media workers in the Bandung region. This research was conducted in several agricultural extension areas in Bandung Regency. The methodology used was a survey with a descriptive quantitative research design. The research used is an analysis of the performance level of agricultural extension workers using a calculator based on the Order Number of the Ministry of Agriculture: 91/Permentan/OT.140/9/2013 and Kendall tau correlation analysis. Based on the evaluation of the performance level, agricultural extension workers in Bandung Regency are in the good sector with an average score of 80.125 and 7 extension workers have performance standards in the good sector and 33 extension workers in the category of good performance value. Based on Kendall Tau correlation analysis, it is known that the factors related to the efficiency level of agricultural extension workers in Bandung Regency are working hours, motivation of extension workers, management support, and availability of resources and equipment. extension project management, communication skills and teamwork skills.